Caffeine for sports performance - Burke, Louise 1959- (Human Kinetics, 2013)
A resource on caffeine and its use and impact on sports performance. Based on research, studies and guidelines, it is suitable for athletes and fitness enthusiasts looking to improve training and competition. It also provides insight into the attitudes towards caffeine and how those attitudes have changed over the years